Y2O3 film as a diffusion barrier between MoSi2 coating and Nb-Si based alloy. (March 2022) - Qiao, Yanqiang; Zhang, Xiao; Guo, Xiping
Abstract: A MoSi2 coating with Y2 O3 diffusion barrier was prepared on Nb-Si based alloy by electroplating of Y and then autoxidation of the Y film, followed by spark plasma sintering (SPS). With the addition of Y2 O3 diffusion barrier, the outward diffusion of Nb, Ti and Cr was greatly suppressed and the inward consumption of Si element was reduced. After exposure of 500 h at 1250 °C, a dense SiO2 scale with a thickness of 5.5–6.7 µm formed on the coating and its mass gain was about 0.9 mg·cm −2 . Highlights: MoSi2 coating with a Y2 O3 diffusion barrier has been prepared. The coating mainly consists of MoSi2 and a small amount of MoB particles. The Y2 O3 diffusion barrier was uniformly located at the interface. The interdiffusion was effectively restrained by the Y2 O3 diffusion barrier. A dense scale formed on the coating after exposure of 500 h.